Diagnostic Accuracy of Post Contrast Magnetic Resonance Imaging for Meningitis Taking Lumbar Puncture as Gold Standard - Mehmood, Sidra; Khan, Mohammad Imran (Indus Journal of Bioscience Research, 2025)
Background: Meningitis is a life-threatening condition that requires early diagnosis and immediate medical attention. MRI detects meningeal enhancement with greater sensitivity and specificity. Objective: The aim of this study was to find out the Diagnostic accuracy of post contrast magnetic resonance imaging for meningitis taking Lumbar puncture as gold standard. Material and Method: The current descriptive Cross-sectional study was carried out at the department radiology in Lady reading hospital Peshawar over a period of 6 months from March 2023 to Aug 2023 after taking approval from the research unit of college of physicians and surgeon of Pakistan and ethical board of the institute. The sample size was find out using WHO calculator .a total of 202 individuals of both gender and different age groups (2-70 years) with suspected meningitis based on clinical presentations were included. Demographic features like gender, age, address of the participants were recorded .physical description and medical history of the patients were also noted. All the participants underwent MRI scan of the brain (vertex to the base of the skull) by using Tesla 1.5 MR unit Syngo.The results were noted. Then the CSF were collected through Lumbar Puncture from each individual. The results of both the MRI and Lumbar Puncture were compared. Data was analyzed through SPSS version 23. Diagnostic accuracy was measured to find the relationship between MRI patterns and cerebrospinal fluid. The sensitivity, specificity and diagnostic accuracy was determined. Results: A total of 202 individuals were enrolled in this study out of which 108(53.4%) were male and 94(46.5%) were females. The mean age of the study population was 25.4±23.5 years. Age wise distribution showed that the most prevalent was younger (17 years or below) (49.5%) followed by age group 18 t0 50 years, 52(25.7%). Clinical presentations among the individuals were Poor feeding, lethargy and irritability 90(45.5%), Headache 85(42.0%), and Nausea /vomiting 20(9.9%). Post contrast MRI results were positive in 96 (47.5%), negative in 106 (52.6%), while lumbar puncture results were positive in 102 (50.4%) and negative in 100 (49.5%). The post-contrast MRI showed 79% sensitivity, 84% specificity, and 80% diagnostic accuracy. Conclusion: Our study concluded that Post-contrast magnetic resonance imaging is the most reliable and effective diagnostic method for detecting meningitis in suspected cases, taking Lumbar puncture as gold standard.